POLA KOMUNIKASI ANTAR BUDAYA DALAM INTERAKSI SOSIAL ETNIS KARO DAN ETNIS MINANG DI KECAMATAN KABANJAHE KABUPATEN KARO - Syafruddin Ritonga Ian Adian Tarigan (PERSPEKTIF, 2012)
Human beings are creatures of God Almighty to the structure functions that are perfectly ringt when compared with other gods creatures, because communication becomes an important element in the whole of human life,then communication itself is inseparable from the history of humanity, the nature of communication process, the structure it is also increasingly complex society, society is also determined by the complexity of cultural diversity and the processes that generad,the community is rich with culture,the more complex social processes that produced,the various communication processes in society related to structrures and layers as well as cultural diversity and social processes that exist in society and dependent on the influence of his audience,whether individuals, groups or society at large.